Using a Realistic Context to Motivate and Teach Engineering Students the Chain Rule - Imad Abou-Hayt; Bettina Dahl (Education Sciences)
Existing research shows that students struggle to understand and use the chain rule appropriately. Other research suggests instructors use more contextually rich problems in their teaching to allow the students to experience calculus through meaningful contexts. In response, this concept paper presents four tasks using the chain rule that we anticipate can be compatible with how students discern concepts, and which could enhance the students’ understanding of the chain rule. The setup is that the students learn the chain rule through the multiplication rule, demonstrated through four teaching tasks. Applying Tall’s three worlds of mathematics when designing mathematics tasks makes it possible to blend symbolic and embodied worlds, opening the door to the formal world, which is beneficial for engineering students.